KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENDUKUNG INOVASI PEMBELAJARAN - Rulli Widiantoro; Sigit Haryanto; Rosyid Ridlo; Suharno; Djalal Fuadi (STKIP Subang, 2026)
Objective: This article aims to examine the role of transformational leadership of school principals in supporting learning innovation and to explain the integration of transformational, instructional, and digital leadership as a strategic approach to improving the quality of learning in schools. Methods: This study employed a narrative literature review by synthesizing relevant peer-reviewed journal articles and scholarly sources on transformational leadership, school leadership, teacher innovation, school culture, professional development, and digital learning. The selected literature was analyzed thematically to identify recurring patterns and develop a comprehensive conceptual synthesis. Results: The findings indicate that transformational school principals strengthen learning innovation by developing a shared vision, demonstrating exemplary leadership, providing inspirational motivation, encouraging intellectual stimulation, fostering professional collaboration, implementing developmental academic supervision, and promoting the pedagogical use of digital technology. These leadership practices also enhance teachers' commitment, creativity, and innovative behavior in the learning process. Novelty: This article proposes an integrated conceptual framework that combines transformational, instructional, and digital leadership as complementary approaches to fostering sustainable learning innovation and offers practical implications for school leaders seeking to strengthen innovation-oriented school culture.